A Precise Description of the Electronic Structures and Spin-Allowed Transition Properties of PF and Its Cation： All-Electron Configuration-Interaction Investigations Including Relativistic Effect - 李奇楠 赵书涛 张晓美 罗旺 李瑞 闫冰 (Chinese physics letters, 2015)
The electronic structures of PF and PF＋ are calculated with the high-level configuration interaction method. To improve the precision of calculations, the spin-orbit coupling effect, the scalar relativistic effect, and the Davidson correction（q-Q） are also considered. The spectroscopic parameters of bound states are derived by the electronic structures of PF and PF＋, which are in good accordance with the measurements. The transition dipole moments of spin-allowed transitions are evaluated, and the radiative lifetimes of several A S states of PF and PF＋ are obtained.